Draft genome sequences of two Sporothrix schenckii clinical isolates associated with human sporotrichosis in Colombia (2018)
Sporothrix schenckii is a thermodimorphic fungal pathogen with a high genetic diversity. In this work, we present the assembly and similarity analysis of the whole-genome sequences of two clinical isolates from Colombia of S. schenckii sensu stricto. © 2018 Gomez et al.